HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN PERILAKU PENCEGAHAN ISPA PADA BALITA - Roslin E. M. Sormin; Matilda Bupu Ria; Muhammad Saleh Nuwa (LPPMK STIKES Widyagama Husada, 2023)
Acute respiratory tract infection (ARI) is still one of the diseases with the highest number of sufferers/patients, this is due to the high mortality rate caused by ARI, especially in toddlers. The impact of this disease on toddlers is a decrease in the immune system, late growth development, and they are vulnerable to suffer from malnutrition and others. The purpose of this study is to identify the knowledge level of mothers about ARI on infants in the work area ofOesapa Community Health Center. This type of descriptive research with a cross sectional sample approach in this study as many as 98 of the population of 134 toddlers with sample techniques using simple random sampling.The instruments used in the questionnaire have been tested for validity and rehabilitation Based on the research results in the work area of Oesapa Community Health Center and the discussion that has been described previously, the following conclusions can be drawn, the mother's knowledge about ARI in infants are in the poor category of 47 respondents (48, 0%), ARI prevention behavior in children or toddlers shows that the majority of respondents have good behavior that is as many as 40 respondents (40.8%), there is a relationship between the level of knowledge with ARI prevention behavior in toddlers. Chi squar statistical test results (ρ) = 0.017 <0.005. is expected to provide useful information and can be used as a material in order to improve health programs for toddlers, especially those related to ARI in Oesapa Community Health Center.